2018
DOI: 10.18295/squmj.2017.17.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Care in Oman: Where do we stand and where should we be heading?

Abstract: NA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…In our study, a higher number of trauma visits was observed among male adults (85.6%), a fi nding that is consistent with different studies [7,9,10] [11]. Patients with stab injuries signifi cantly required more resuscitation, 31.5 minutes (P= 0.038).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, a higher number of trauma visits was observed among male adults (85.6%), a fi nding that is consistent with different studies [7,9,10] [11]. Patients with stab injuries signifi cantly required more resuscitation, 31.5 minutes (P= 0.038).…”
Section: Discussionsupporting
confidence: 91%
“…In most healthcare systems worldwide, trauma centres are designated at different levels according to their capacity to treat critically injured patients, with level I centres typically being considered most capable and level III centres being least capable. 9 Generally, higher-level trauma centres provide the greatest level of care and have access to specialised trauma surgeons (i.e. neurosurgeons and orthopaedic surgeons) and nurses as well as trauma-specific diagnostic equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emergency medical services are often the first point-of-care for critically injured patients and would transfer such patients immediately by ambulance to a trauma centre. 9 These factors might thus partly explain the lack of availability of certain types of equipment in primary health care centres. Nevertheless, in many trauma cases, immediate management can mean the difference between life or death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations